Perinatal outcomes among twin pregnancies with gestational diabetes mellitus: A nine-year retrospective cohort study - Lin, Dongxin; Fan, Dazhi; Li, Pengsheng; Chen, Gengdong; Rao, Jiaming; Zhou, Zixing; Zhang, Huishan; Luo, Xin; Ma, Huiting; Feng, Jingping; Lu, Demei; Wang, Lijuan; et al. (Frontiers in Public Health, 2022)
Objective To compared the outcomes between gestational diabetes mellitus (GDM) versus non-GDM twin gestations. Methods A retrospective cohort study of 2,151 twin pregnancies was performed in a tertiary hospital in Foshan, China, 2012-2020. Pregnancy and neonatal outcomes were compared between women with versus without GDM using 1:1 propensity score matching (PSM) and multivariable logistic models. For neonatal outcomes, generalized estimating equation (GEE) approach was used to address the intertwin correlation. Results Of the 2,151 participants, 472 women (21.9%) were diagnosed with GDM. Women with GDM were older and had higher incidence of overweight or obesity, chronic hypertension, assisted pregnancies and dichorionic twins. The incidence of pregnancy-related hypertensive disorders was similar (10.0% vs. 11.7%, P=0.300). In the PSM cohort of 936 pregnancies, there was no statistical difference when comparing GDM twin pregnancies and non-GDM for any of the obstetric and neonatal outcomes, especially in terms of preterm birth, neonatal weight outcomes and respiratory morbidities. Similar results were obtained from multivariable logistic models adjusted for confounders. Conclusion Twin pregnancies with GDM have comparable obstetric and neonatal outcomes to those without. Individualized diagnostic criteria and prenatal management among GDM twin pregnancies different from singletons deserve to be further discussed.